Single Tariff and Tax Compliance of Micro Small and Medium Enterprises in Indonesia (Case Study in DKI Jakarta Province) - Guztaman, Muhammad Yudhy; Djamaluddin, Sartika (Proceeding UII-ICABE, 2020)
To increase tax ratio and tax basis, Government release Peraturan Pemerintah (PP) No. 46 Tahun 2013. Using single tariff (1%), the regulation gives easiness to tax payer (Micro, Small and Medium Enterprises) in order to fulfill their tax obligation. After five years implementation, Government revised the policy. Peraturan Pemerintah No. 23 Tahun 2018 not only decrease the tariff (0,5%) but also regulate time limit using the tariff. Furthermore, the policy gives tax payers a freedom to choose using special (single) tariff or regular one (progressive tariff) but they could not use single tariff if they already use progressive tariff (vice versa). This paper will show the changes in MSME taxpayers (corporate and personal tax payer) behavior in DKI Jakarta Province responding the regulation. Keywords: Tax Compliance, Micro, Small and Medium Enterprise, Single Tariff